Analisis Yuridis Child Grooming di Media Sosial Berdasarkan Qanun Aceh: Legal Analysis of Child Grooming on Social Media Based on Aceh Qanun - Amalia Lillah; Abdul Wahab (CLEAR: Criminal Law Review, 2026)
Child grooming is a sexual crime against children that involves a psychological approach and manipulation, especially through social media. Children are increasingly vulnerable because of the difficulty of supervision in the digital world. In Indonesia, the law does not yet clearly regulate childcare as a criminal offense, including in the Aceh Qanun. This research analyzes forms of child grooming on social media and their regulation in Aceh, using normative legal research methods. The results show the stages of child care and the need to strengthen child protection regulations. It is hoped that this research can help develop Islamic criminal law and determine legal policies in Aceh regarding child protection. Child grooming adalah kejahatan seksual terhadap anak yang melibatkan pendekatan dan manipulasi psikologis, terutama melalui media sosial. Anak-anak semakin rentan karena sulitnya pengawasan di dunia digital. Di Indonesia, hukum belum mengatur child grooming sebagai tindak pidana yang jelas, termasuk dalam Qanun Aceh. Penelitian ini menganalisis bentuk-bentuk child grooming di media sosial dan pengaturannya di Aceh, menggunakan metode penelitian hukum normatif. Hasil menunjukkan tahapan child grooming dan perlunya penguatan regulasi untuk perlindungan anak. Penelitian diharapkan dapat membantu pengembangan hukum pidana Islam dan penentuan kebijakan hukum di Aceh terkait perlindungan anak.